2020
DOI: 10.3390/ijms21239119
|View full text |Cite
|
Sign up to set email alerts
|

Connexins—Therapeutic Targets in Cancers

Abstract: Connexins (Cx) are members of a protein family that forms intercellular channels localised in gap junction (GJ) plaques and single transmembrane channels called hemichannels. They participate in intercellular communication or communication between the intracellular and extracellular environments. Connexins affect cell homeostasis, growth and differentiation by enabling the exchange of metabolites or by interfering with various signalling pathways. Alterations in the functionality and the expression of connexin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 163 publications
0
14
0
Order By: Relevance
“…However, this scientific area is quite poorly studied and further, we focus on the direct or indirect involvement of cholesterol precursors in cancers. We found that cholesterol precursors can be formally divided into three groups ( Table 4 ) depending on their impact on carcinogenesis [ 50 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this scientific area is quite poorly studied and further, we focus on the direct or indirect involvement of cholesterol precursors in cancers. We found that cholesterol precursors can be formally divided into three groups ( Table 4 ) depending on their impact on carcinogenesis [ 50 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 ].…”
Section: Discussionmentioning
confidence: 99%
“…The functional modulation of GJs, inhibition as well as enhancement, has been proposed as a novel strategy for the treatment of various diseases. These include cardiac diseases, such as arrhythmias, remodeling after cardiac infarction, and atherosclerosis [ 33 , 34 ], brain diseases, e.g., epilepsy and neurodegenerative diseases [ 35 , 36 ], and even cancer [ 37 ]. Notably, a recent study suggested that loss of GJ coupling represents a cause of human temporal lobe epilepsy [ 38 ].To identify novel GJ modulators, a suitable assay for compound screening was required.…”
Section: Discussionmentioning
confidence: 99%
“…Cxs are transmembrane proteins, which are responsible for intercellular communication ( 38 ). Cx43, a member of the Cx family, has been identified as the main component of the gap junction channels in astrocytes.…”
Section: Discussionmentioning
confidence: 99%